2005
DOI: 10.1111/j.1600-0528.2005.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Routine oral examination: differences in characteristics of Dutch general dental practitioners related to type of recall interval

Abstract: Dutch GDPs differ in the way they deal with the determination of recall interval frequency. These are also specific differences in performance and opinions regarding ROE. With the changing prevalence of oral diseases and the skewed distribution within populations, further research is advocated on consistent decision making to determine the most appropriate recall policy in preventing oral disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Based on previous research, 10,23 GDPs attitude towards periodontal screening showed to be a salient determinant of individualised assessment and assignment of variable recalls. In an elderly population (65% of the patients were older than 35 years of age), the risk of developing a periodontal condition is increased.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on previous research, 10,23 GDPs attitude towards periodontal screening showed to be a salient determinant of individualised assessment and assignment of variable recalls. In an elderly population (65% of the patients were older than 35 years of age), the risk of developing a periodontal condition is increased.…”
Section: Discussionmentioning
confidence: 97%
“…The explorative nature of this clinical case recording study provides a better insight in individual behaviour of GDPs, compared to data obtained from general ROE-questionnaires. 23,28 To measure clinical performance, several data sources, including their flaws, have been described, including medical record reviews, and health insurance company databases. [34][35][36] Although not formally validated, it leads to reasonably valid recording.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…General dental practitioners (GDPs) still assign standardised recall periods for all regular attendees. 9,10 Fuelled by quality of care aspects, GDPs are being confronted with new patient-tailored surveillance approaches. They have not been trained to screen systematically high-and lowrisk patients.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that many healthy individuals are scheduled for routine oral screening. In 2000, 50% of the Dutch GDPs assigned all their regular patients for ROE twice a year [2], irrespective of level of risk for oral disease. The efficiency of this systematic monitoring system is still disputed in The Netherlands, as well as internationally [3-10].…”
Section: Introductionmentioning
confidence: 99%